The Relation of Personality Traits to Internet Addiction and Internet Social Behaviour in Chinese Secondary School Students - Chen, Eve Siu Ling (Advances in Social Sciences Research Journal, 2021)
The present study attempts to study the relationship between internet addiction and internet social behaviour with personality. The sample consisted of 365 Grade 10 students from two secondary schools in Mainland China. Four instruments were used: Young’s Internet Addiction Test, Chen Internet Addiction Scale, Ma, Li & Pow’s Adolescent Internet Use Questionnaire, and Eysenck Personality Questionnaire. Boys scored significantly higher than girls in the two Internet addiction questionnaires. Results also supported the following hypotheses: (1) Internet addiction is positively associated with psychoticism, neuroticism, and frequency of Internet use; and it is also negatively associated with social desirability and self-concept. (2) Holistic Internet social behavior is positively associated with extroversion, social desirability, self-concept, and frequency of Internet use; and it is also negatively associated with psychoticism and neuroticism. A high (low) rating of Holistic Internet Social Behavior refers to a high (low) rating of Prosocial Internet Behaviour and a low (high) rating of Antisocial Internet Behaviour.